Can elongation of the ileum by epiploic appendagitis result in acute abdomen? - Doğan Yıldırım; Ahmet Kocakuşak; Adnan Hut; Mikail Çakır (Turkish Journal of Gastroenterology, 2019)
Cite this article as: Yıldırım D, Kocakuşak A, Hut A, Çakır M. Can elongation of the ileum by epiploic appendagitis result in acute abdomen? Turk J Gastroenterol 2018; 29: 370-2.